Laboratory Identification of Donor‐Derived Coxsackievirus B3 Transmission. Issue 2 (12th January 2015) - Abbott, I. J.; Papadakis, G.; Kaye, M.; Opdam, H.; Hutton, H.; Angus, P. W.; Johnson, P. D. R.; Kanellis, J.; Westall, G.; Druce, J.; Catton, M.
<x xml:space="preserve">Abstract</x> Unexpected donor‐to‐recipient infectious disease transmission is an important, albeit rare, complication of solid organ transplantation. Greater work and understanding about the epidemiology of these donor‐derived transmissions is continually required to further mitigate this risk. Herein we present the first reported case of proven donor‐derived transmission of coxsackievirus serogroup‐3, an enterovirus, following solid organ transplant. Swift and effective communication between the organ donation agency, treating physicians, laboratory testing and notification ensured a coordinated approach. The resulting clinical syndromes in the organ recipients were mild. This case highlights the requirement for ongoing surveillance over a broad range of infecting pathogens that may present as a donor‐derived infection.